8v-3v-3+7v simplified

Answers

Answer 1
Answer:

Your answer is 12v-3.

-

Steps:

1. Group Like Terms. (8v-3v+7v-3)

2. Add Similar Elements. (8v-3v+7v=12v)

3. Finished. (=12v-3)

-

Hope this helped :)


Related Questions

8 yards is equal less or greater than 20 feet
Jill’s front door is 42” wide and 84” tall. She purchased a circular table that is 96 inches in diameter. Will the table fit through the front door?
100 cm is equal to: 0.1 m 1 m 10 m 1,000 m
gloria earned $26 for babysitting 4 hours. write and solve an equation in the form of y= kx, where y refers to dollars and x refers to hours worked, to determine how much gloria would earn after babysitting 25 hours.
How many more stickers does maddie's have on her notebook than on meg's note book

Angelo ride his bike around a bike trail that was 1/4 of a mile long.he rode his bike around the trail 8 times .Angelo says he rode a total of 8/4 miles

Answers

Angelo rode his bike around the bike trail for 2 miles , 8 x 1/4 = 8/4 = 2 miles
all u have to do is 1/4×8 =8/4so he is correct

IS 71 OVER 20 SIMPLEST FORM?IF NOT WHATS THE ANSWER?

Answers


71/20 is not in simplest form because you need to change it into a mixed number by dividing 71 and 20 and putting the remainder over 20.
no, simplest for would be 3 and eleven twentieths

Steven has a rectangular closet the length is 10 feet and the width is 48 inches determine the area of the closet in square feet

Answers

To be honest with u I think that u need to multiply 10 times 48.. I think thats it not sure if is the 100% correct answer

Whats the answer to 29-(2c+3)=2(c+3)+c

Answers

Answer:

29-(2c+3)=2(c+3)+c=

We move all terms to the left:

29-(2c+3)-(2(c+3)+c)=0

We get rid of parentheses

-2c-(2(c+3)+c)-3+29=0

Step-by-step explanation:

Answer:

Solution for 29-(2c+3)=2(c+3)+c equation:

Simplifying

29 + -1(2c + 3) = 2(c + 3) + c

Reorder the terms:

29 + -1(3 + 2c) = 2(c + 3) + c

29 + (3 * -1 + 2c * -1) = 2(c + 3) + c

29 + (-3 + -2c) = 2(c + 3) + c

Combine like terms: 29 + -3 = 26

26 + -2c = 2(c + 3) + c

Reorder the terms:

26 + -2c = 2(3 + c) + c

26 + -2c = (3 * 2 + c * 2) + c

26 + -2c = (6 + 2c) + c

Combine like terms: 2c + c = 3c

26 + -2c = 6 + 3c

Solving

26 + -2c = 6 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.

26 + -2c + -3c = 6 + 3c + -3c

Combine like terms: -2c + -3c = -5c

26 + -5c = 6 + 3c + -3c

Combine like terms: 3c + -3c = 0

26 + -5c = 6 + 0

26 + -5c = 6

Add '-26' to each side of the equation.

26 + -26 + -5c = 6 + -26

Combine like terms: 26 + -26 = 0

0 + -5c = 6 + -26

-5c = 6 + -26

Combine like terms: 6 + -26 = -20

-5c = -20

Divide each side by '-5'.

c = 4

Simplifying

c = 4

brian filled 72 glasses with apple juice for a school party if each glass holds 1 cup of juice how many quarts of apple juice did brian use

Answers

4 cups in a quart so you would have 72 cups divided by 4 and get 18

Answer: 18

Step-by-step explanation:

72 Divided by 4 = 18

A company shipped 48 boxes of canned dog food each box contains 24 cans how many cans of food did the company ship in all

Answers

To do this you have to multiply 48 by 24.  This will give you 1,152.  They shipped 1,152 cans of food in all.
You would have to multiply 48 * 24 and the answer is 1152